Clinical features and outcomes of patients with myositis associated-interstitial lung disease - Karampitsakos, Theodoros; Tzilas, Vasilios; Papaioannou, Ourania; Chrysikos, Serafeim; Vasarmidi, Eirini; Juge, Pierre-Antoine; Vizirianaki, Styliani; Bibaki, Eleni; Reppa, Argyro; Sidiropoulos, Prodromos; Katsaras, Matthaios; Sotiropoulou, Vasilina; et al. (Frontiers in Medicine, 2023)
Introduction Myositis associated interstitial lung disease (ILD) seems to be an under-recognized entity. Methods In this multicenter, retrospective study, we recorded between 9/12/2019 and 30/9/2021 consecutive patients who presented in five different ILD centers from two European countries (Greece, France) and received a multidisciplinary diagnosis of myositis associated-ILD. The primary outcome was all-cause mortality over 1 year in specific subgroups of patients. Secondary outcomes included comparison of disease characteristics between patients diagnosed with the amyopathic subtype and patients with evidence of myopathy at diagnosis. Results We identified 75 patients with myositis associated-ILD. Median age (95% CI) at the time of diagnosis was 64.0 (61.0–65.0) years. Antinuclear antibody testing was positive in 40% of the cohort (n = 30/75). Myopathy onset occurred first in 40.0% of cases (n = 30), ILD without evidence of myopathy occurred in 29 patients (38.7%), while 16 patients (21.3%) were diagnosed concomitantly with ILD and myopathy. The commonest radiographic pattern was cellular non-specific interstitial pneumonia (NSIP) and was observed in 29 patients (38.7%). The radiographic pattern of organizing pneumonia was significantly more common in patients diagnosed with the amyopathic subtype compared to patients that presented with myopathy [24.1% (n = 7/29) vs. 6.5% (n = 3/46), p = 0.03]. One year survival was 86.7% in the overall population. Kaplan–Meier analysis demonstrated significantly higher all-cause 1-year mortality in patients with the amyopathic subtype compared to patients with evidence of myopathy [H R 4.24 (95% CI: 1.16–15.54), p = 0.03]. Patients diagnosed following hospitalization due to acute respiratory failure experienced increased risk of 1-year all-cause mortality compared to patients diagnosed in outpatient setting [HR 6.70 (95% CI: 1.19–37.81), p = 0.03]. Finally, patients with positive anti-MDA5 presented with higher 1-year all-cause mortality compared to anti-MDA5 negative patients [HR 28.37 (95% CI: 5.13–157.01), p = 0.0001]. Conclusion Specific ILD radiographic patterns such as NSIP and organizing pneumonia may herald underlying inflammatory myopathies. Hospitalized patients presenting with bilateral organizing pneumonia refractory to antibiotics should be meticulously evaluated for myositis associated-ILD even if there is no overt muscular involvement. Incorporation of ILD radiological patterns in the diagnostic criteria of inflammatory myopathies may lead to timely therapeutic interventions and positively impact patients’ survival.